PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP PENINGKATAN KEMAMPUAN HOTS MATEMATIS SISWA - Pattimukay, Nessy; Takaria, Johannis; Rumsifa, Benedikta (Almeera Education, 2025)
The purpose of this study was to determine the effect of the Guided Discovery Learning (GDL) learning model on improving students' Higher Order Thinking Skills (HOTS) abilities. The method used is quantitative descriptive with a Quasi-experimental approach with a pretest-posttest experimental design type. The study involved 25 fifth grade students of SD Teladan Ambon as samples. The results showed that there was an effect of the GDL learning model on improving students' HOTS abilities. The increase in HOTS abilities increased in the high category with an N-gain value of 0.8 for 1 student, a medium category of 0.56 for 19 students, and a low category of 0.20 for 5 students. The increase was due to the effective use of the GDL model, where this model trains students' critical thinking and problem-solving skills related to flat shapes. Students can also analyze, evaluate, and create or create about flat shapes well.